Pengaruh Manajemen Peserta Didik terhadap Tingkat Kedisiplinan Siswa Kelas IX di Sekolah Menengah Atas Negeri 1 Kecamatan Pasir Penyu Indragiri Hulu. - Afrida Yanis (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research is based on the problem of low obedience and compliance of students in carrying out discipline at State Senior High School 1, Pasir Penyu Indragiri Hulu District. This study aims to find out that there is a significant influence of student management on the level of discipline of grade IX students at State Senior High School 1, Pasir PenyuIndragiri Hulu District. The research method used is the quantitative research method. Data collection uses observation, questionnaires, interviews and documentation. The research population was 60 people. The data analysis technique used is product moment correlation and multiple linear regression. To analyze the data using the IBM SPSS 25 Software program. The results of the study are first: There is a significant influence of student management on the level of discipline of grade IX students at State Senior High School 1, Pasir PenyuIndragiri Hulu District, because the results of the hypothesis test in the product moment analysis, a correlation coefficient value of 0.439 (calculated) > 0.254 (table) and a significance of 0.000 < 0.05 which means that there is a significant correlation of student management to the level of student discipline with a The relationship between variables is located at 0.41 – 0.60 which means it belongs to the category of moderate correlation. Then, based on the results of the regression equation calculation, the prediction of the value of the Y variable that is influenced by the X variable optimally is 26.432. This means that when the student management variable will increase by 18.88. Meanwhile, when the variable of student management is optimally increased, which is 40 points, the variable of the level of discipline of grade IX students will increase by 107,423. And based on the t-test, a regression coefficient value of 3,720 was obtained with a significance of 0.000 < 0.05. Therefore, it can be concluded that there is a significant influence of student management on the level of discipline of grade IX students at State Senior High School 1, Pasir Penyu Indragiri Hulu District.